Software to build network frames, with GUI, CLI and programming library - López Muñoz, Marta Lucia; Carrillo Valderrama, José Luis Alejandro (Ingeniería Solidaria, 2019)
Introduction: This publication is the product of a research project named “Design and implementation of a software to build network frames with CLI, GUI interface and programming library” of the Corporación Politécnico de la Costa Atlántica in Barranquilla, Colombia between the year 2016 and 2018. A piece of software with multiplatform capability, GUI, CLI and programming library was developed. The software allows for the intuitive construction of network frames, speeding up construction times, thus facilitating practical learning of the concept of encapsulation networking.Objective: The research aims to build a multiplatform computing solution, with a GUI, CLI and programming library, in order to build network frames intuitively.Methodology: The scope of the project is descriptive, since the development includes the analysis and implementation of the software and its components; as well as functional tests.Results: The software was built according to the phases proposed in the methodology. A high percentage of students obtained average scores in the evaluation carried out on frames, packages and segments.Conclusion: The results demonstrate the need to apply a new teaching methodology based on the elaboration of frames, to improve the learning process in computer networks.Originality: A software solution that complements existing limitations in portability, versatility and ease of use is proposed. This solution is applicable both in the workplace and in the educational field.Limitations: The processes of sending and capturing frames are separated in the software, meaning that TCP communication cannot be maintained. It is necessary to build a GUI application to capture network frames and not depend on a tool like Wireshark for visualizing the frames.
Keywords: frame; encasulaption; network computers; software; teaching